A Savant Case from Turkey: Cognitive Functions and Calendar Calculation - Bıçakçı, Mehmet; Köksal, M.S.; Baloğlu, M. (Clinical Psychology and Special Education, 2021)
The current study is the first detailed report on a savant case in Turkey. We collected data from a 25-year-old-male savant on attention span, short-term memory, working memory, autobiographical memory, overall intelligence, reading speed, text interpretation, and advanced calendar calculation. Data collection tools included the Test of Nonverbal Intelligence (4th edition), Wechsler Adult Intelligence Scale-Revised, Stanford-Binet 5 Working Memory Test and Raven's Colored Progressive Matrices for assessing general intellectual functioning; the Verbal Short-Term Memory Test for assessing memory assessment; d2 for assessing attention; a structured reading text; family interview protocols; and an individual interview protocol. The savant has a composite intellectual level of 85 and was recently diagnosed with pervasive developmental disorder when he was 25 years old. He evidenced limited attention span but excellent short-term memory, working memory, autobiographical memory and calendar calculation.
Keywords: Savant syndrome; splinter savant skills; calendar calculation.

BRIDGING THE MISSING LINK ON GIFTEDNESS AND UNDERACHIEVER LABELS RESEARCH: EMBRACING SYMBOLIC INTERACTIONISM - Bicakci, Mehmet (Essential Issues in Symbolic Interaction, 2024)
In this chapter, I will outline the labels of giftedness and underachievement and present the theoretical debates surrounding these labels. A historicist examination of these labels follows, highlighting how the gifted underachievement (GUA) label emerges through the negation of “giftedness.” Subsequently, I explore the concept of GUA and its negative connotations, stemming from the positive valuation inherent in the term “giftedness” and its implications for what is considered “normal.” This chapter also reviews perspectives on shifting the focus away from the individual within the current paradigm of labeling giftedness and explores insights from systemic thinking and symbolic interactionism (SI). The conclusion underscores the necessity of a symbolic interactionist perspective to address the gaps in research on the labeling of giftedness and underachievement. Finally, I propose a generic definition that can be used in GUA research in the light of SI.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Gifted underachievement; Pygmalion effect; self-concept; self-fulfilling prophecy; teacher-student interaction

Creativity in Research with Gifted Samples in Turkey - Bicakci, Mehmet; Baloglu, Mustafa (Inonu University Journal of the Faculty of Education, 2018)
Özel yeteneklilerin yaratıcılık becerileri üzerine birçok araştırma yapılmasının sebebi, yaratıcılığın bu bireylerin temel özelliklerinden biri olarak anılmasından kaynaklanmaktadır. Bu nitel doküman analizi çalışmasının amacı, Türkiye’deki özel yetenekli öğrencilerin yaratıcılık beceriler üzerine yapılan çalışmaları incelemektir. Literatür taraması sürecinde, elektronik veri tabanlarının gözden geçirilmesi araştırmaların başlıklarında, özetlerinde ya da anahtar kelimelerinde özel yetenekli (gifted/talented), yaratıcı düşünme (creative thinking) ve yaratıcılık (creativity) kelimelerinin kullanımı ile yapılmıştır. Tarama sonucunda, dışlama ve dahil etme kriterlerine uyan çalışmaların seçilmesinin ardından 12 doktora tezi, altı yüksek lisans tezi ve üç araştırma makalesi olmak üzere toplam 21 çalışmaya ulaşılmıştır. Türkiye’deki özel yeteneklilerin yaratıcılık becerileri üzerine yapılan bu araştırmalardan 18’i deneysel desende gerçekleşirken, üçü diğer nicel araştırma desenleri ile yapılmıştır. Doküman incelemesinin ardından elde edilen verilere göre bu çalışmalarda dört kez Yaratıcı Düşünme – Şekilsel Üretim Testi, iki kez Yaratıcılık Ölçeği (How Creative Are You?) ve 16 kez Torrance Yaratıcı Düşünme Testi kullanılmıştır. Araştırmaların çoğu 2011-2014 yılları arasında yapılmıştır. Güncel araştırmalara ihtiyaç duyulduğu söylenebilir. <br

Effect of peer delivered social stories on the crossing skills of primary school students with developmental disabilities - Bıçakçı, Mehmet; Gül, Seray Olçay (Egitim Ve Bilim-Education and Science, 2019)
In this study, it was aimed to examine the effect of a peer education program developed on the acquisitions of knowledge and skill of writing and implementing social stories by students attending primary school, and the effect of social stories delivered by peers who have completed the program (peer tutor) on the acquisition of crossing skills by students with developmental disabilities (peer tutees), maintenance of this skill two weeks after the end of the implementation, and generalization with a different street. In the study, social validity data were collected from peer tutees and peer tutors using a subjective evaluation approach. The study was carried out with a total of six participants consisting of three students aged between 7 and 9 years who attend a primary school in a province in East Anatolian Region, two of whom are diagnosed with autism spectrum disorder and one of whom is diagnosed with a mild intellectual disability, and these students' peers with normal development. Peer tutees were taught how to write and deliver social stories with one-on-one instruction by following the steps of Powerpoint presentation, modeling, experimenting, and providing feedback. In the study, a multiple probe design with probe conditions across dyads (peer tutor - peer tutees), one of the single subject research models, was used to evaluate the effect of social stories written and delivered by peer tutors on peer tutees' learning crossing skills. Research results showed that peer tutors acquired the social story writing and implementation skill accurately by 100%. After the instruction delivered by the peers who acquired the social story writing and implementation skill, it was observed that peer tutees acquired the crossing skill and could generalize it to a different street, and that two peer tutees with the ASD continued to exhibit this skill they acquired accurately by 100% two weeks after the end of the study. Maintenance data were not collected from the third peer tutee due to the closure of schools. Social validity data collected from peer tutees and peer tutors using a subjective evaluation approach showed that both peer tutees and peer tutors had positive opinions on the target skill, social stories, and research results. These results were discussed within the context of the literature, and suggestions were made to include peer mediated implementations in teaching different skills with different methods and to make the use of social stories in teaching safety skills by parents, siblings, specialists working in the field and teachers widespread.
Created from Fastlane, Scopus look-up
Keywords: Individuals with developmental disabilities; Pedestrian skills; Peer-mediated implementations; Safety skills; Social stories

Exploring the Relationship between Socioeconomic Status and Identification of Gifted in Turkey through Critical Systems Thinking - Bıçakçı, Mehmet (Hacettepe Universitesi Egitim Fakultesi Dergisi-Hacettepe University Journal of Education, 2023)
This correlational study examines the relationship between identification as gifted and various indicators of socioeconomic status (SES) among high school students living in Turkey. The relatively large and representative sample consists of 688 high school students, both identified (n = 343) and unidentified (n = 345) as gifted, enrolled in nationwide after-school gifted education programs. The “identified” group comprises adolescents who scored an IQ index of 130 or higher, while the unidentified group comprises high school students attending formal educational institutions without meeting the IQ-based identification criterion. Chi-square tests of independence were utilized to investigate the relationship between identification status and SES indicators such as perceived household income, parental education level, current area of residence, and area of residence where most of life is spent. The results indicate that identified participants are more likely to come from families with higher perceived income and parental education levels, live in urban areas, and spend most of their lives in urban areas compared to the unidentified group. Overall, the findings suggest that SES factors might play a significant role in the identification of giftedness students in Turkey. The findings are discussed around the problem of underrepresentation in traditional identification methods, with a focus on educational equality within the framework of systems theory and critical systems theor
Keywords: Low representation group; equality; gifted and talented; socioeconomic status

Full-time Schooling for Gifted Students in Turkey: What Teachers and Experts Say about This? - Yüreğilli, G.D.; Şakar, S.N.; Bıçakçı, Mehmet; Köksal, M.S. (Clinical Psychology and Special Education, 2021)
This study aimed at investigating suggestions provided by gifted education teachers and experts about full-time schooling for gifted students. In this study qualitative survey method was used and data was collected by an open-ended survey and semi-structured interviews. The data was analyzed by descriptive analysis including coding and categorizing. Using purposive sampling 341 teachers and 3 experts were selected for this study. The findings revealed that the experts suggested disciplinary and theme-oriented curriculum while the teachers suggested flexible and mixed-type curriculums. The experts and teachers suggested different ideas for outcome of the curriculum of the school, life skills and thinking skills component of the curriculum, features of classroom environment, physical conditions and technical equipment, and evaluation of learning in a full-time gifted school. The findings have merit to represent the general picture for starting a new full-time gifted school and contribute to the literature, authorities and families about necessity of this refor
Keywords: Full-time schooling; gifted education; teachers of gifted students; experts of gifted education; qualitative survey method; need analysis.

Üstün Zekâlılarda Beklenmedik Düşük Başarı (BDB): Özellikler, Etken Faktörler ve Müdahale - Bıçakçı, Mehmet; Baloglu, Mustafa (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Özel Eğitim Dergisi, 2021)
Beklenmedik düşük başarı (BDB), beklenen ile gözlenen performans arasındaki fark olarak tanımlanmaktadır. Bu çalışmanın amacı, üstün zekâlılarda BDB’yi ele alarak, kavramla ilişkili tanımları, ölçütleri ve güncel araştırmaları incelemektir. Araştırma, konu hakkında sistematik bir literatür taraması sonrası hazırlanan bir derlemedir. BDB’ye etki eden faktörler arasında, ailevi (ev-içi), kişisel ve okul ile ilgili faktörler ana etkenler olarak öne çıkmaktadır. BDB’ye yönelik müdahalelerde, mentörlük, aile danışmanlığı ve öğretmen desteği gibi uygulamalar literatürde öne çıkmaktadır. BDB’ye yönelik müdahale araştırmalarına önem verilmesi, birey hakkında farklı bilgi kaynaklarına başvurarak, karma yöntemlerle ve bireyi bütüncül olarak ele alan araştırmalara olan ihtiyaç bu çalışma sonucunda ulaşılan göstergelerdi
Keywords: üstün yetenekliler; beklenmedik düşük başarı; akademik başarı; derleme

Üstün Zekalıların Kişilik Özellikleri Üzerine Yapılan Araştırmaların Bibliyometrik Analizi (1957-2020) - Bıçakçı, Mehmet; Baloglu, Mustafa (Uludağ Üniversitesi İlahiyat Fakültesi Dergisi, 2021)
This descriptive study aims to present a bibliometric analysis of research published between 1957 and 2020 on the personality traits of gifted individuals. An electronic search was conducted with Web of Science indexes on June 20, 2020, between 10:00 and 15:00 (GMT +3) without year and language restrictions. This electronic search yielded 321 studies meeting the inclusion criteria. The most frequent language of publication was English (n = 272), and the most frequent country of publication was the USA (n = 131). The number of authors of the 321 documents was 615, and the number of citations was 3,921 (mean annual citation number = 63). 2017 had the highest frequency of publication (n = 29, 9%). The most common Web of Science category was Educational Psychology (f = 98, 30.5%), the most common document type was research article (f = 262, 81.6%), and the most frequently encountered journal Gifted Child Quarterly (between 1971-2017, f = 37,12%). Johns Hopkins University was the most frequent source of the research (n = 11, 3.4%). Findings show that there has been an expansion in the subject network and interdisciplinary studies with a quantitative increase in the last 10 years. As a result of the bibliometric mapping of the studies, it can be said that the studies have just completed the Baconian (basic research and routine studies) period and have passed to the Newtonian (in-depth study and expansion) peri
Keywords: Scientometrics; citiation; talented; gifted; big five